2015
DOI: 10.4172/2375-4494.1000209
|View full text |Cite
|
Sign up to set email alerts
|

Child, Adolescent and Young Adult Suicides: A Comparison Based on the Queensland Suicide Registry

Abstract: Objective: The incidence of suicides increases rapidly up to the age of 20 years. Despite major developmental changes, only a limited number of studies has compared characteristics of child, adolescent and young adult suicides. The aim of the current study was to compare demographic, psychosocial and psychiatric characteristics of suicides in three youngest age groups -10-14 years, 15-19 years and 20-24 years -in Queensland, Australia, between 2002 and 2011. Methods:The Queensland Suicide Register (QSR) contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“… 16 For example, Kawashima 16 studied suicide attempters in Japan and found that risk factors for adolescent women suicide attempters were school problems and parent loss while those for their adult counterparts were a history of mental disorders. Similarly, Kolves and De Leo 17 studied suicides in Australia and reported that suicides in adolescents were highly impacted by family conflicts and school problems while those in adults were highly impacted by psychiatric disorders such as unipolar depression, bipolar disorder, and anxiety disorder. In addition to their findings on high-level differences between adult and adolescent suicides, considering social media use to explain the difference between the groups is highly important.…”
Section: Introductionmentioning
confidence: 99%
“… 16 For example, Kawashima 16 studied suicide attempters in Japan and found that risk factors for adolescent women suicide attempters were school problems and parent loss while those for their adult counterparts were a history of mental disorders. Similarly, Kolves and De Leo 17 studied suicides in Australia and reported that suicides in adolescents were highly impacted by family conflicts and school problems while those in adults were highly impacted by psychiatric disorders such as unipolar depression, bipolar disorder, and anxiety disorder. In addition to their findings on high-level differences between adult and adolescent suicides, considering social media use to explain the difference between the groups is highly important.…”
Section: Introductionmentioning
confidence: 99%
“…Suicide is one of the leading causes of mortality in young people worldwide, ranking second for ages 10-24 years and taking more lives than any one disease-related cause (Patton et al, 2009). While suicide is rare in childhood and early adolescence (Sheftall et al, 2016), there is a sharp increase in rates during mid-adolescence to young adulthood, especially in boys (Kõlves & De Leo, 2015;Malone et al, 2013;McLoughlin et al, 2015;Nock, Borges, Bromet, Cha, et al, 2008). Such a rapid increase suggests that the transition from adolescence to early adulthood is a period of heightened vulnerability to suicide.…”
Section: Introductionmentioning
confidence: 99%